2006
DOI: 10.1021/nl061669s
|View full text |Cite
|
Sign up to set email alerts
|

Large Area, 38 nm Half-Pitch Grating Fabrication by Using Atomic Spacer Lithography from Aluminum Wire Grids

Abstract: We wrapped 150 nm period aluminum wire grid polarizer (WGP) with AlSiOx by using atomic layer deposition at 250 degrees C. The nanometer precision coating defined the spacer to double the spatial frequency of the 100 mm diameter grating fabricated by using a legacy immersion holography setup at 351 nm wavelength. Half-pitch grating of approximately 38 nm was demonstrated with good pattern uniformity, excellent repeatability, and a wide processing window. We believe 10 nm half-pitch grating over even larger are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…In Figure S1(d), a XeF 2 gas phased etch is used to etch the Poly Si only, thus leaving free-standing Al 2 O 3 cylindrical shells on the wafer surface. [23,24,34] Next, in Figure S1 Images of the device during and after fabrication are shown in Figure S2. In Figure S2(a) the photoresist is patterned with a square checkerboard photomask with a period 0.6 µm.…”
Section: Wafer-scale Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…In Figure S1(d), a XeF 2 gas phased etch is used to etch the Poly Si only, thus leaving free-standing Al 2 O 3 cylindrical shells on the wafer surface. [23,24,34] Next, in Figure S1 Images of the device during and after fabrication are shown in Figure S2. In Figure S2(a) the photoresist is patterned with a square checkerboard photomask with a period 0.6 µm.…”
Section: Wafer-scale Fabricationmentioning
confidence: 99%
“…[2,22] Photos and SEM images of the 3 device are shown in Figure 1(c)-(f) where the multilayered structure was fabricated using the sidewall lithography technique across a 6" wafer (see supporting information). [23][24][25] cut-off frequency, the design of the cavities is also based on Q-matching formalism where maximum absorption occurs when the radiative Q rad and the absorption Q abs are equal. [22,26] The measured absorption spectrum shown in MDPhC layer agrees well with experiment, but diverges for , where transmission through the metal layer can no longer be assumed to be .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the fabrication process, the thickness of the deposited metal layer (30 nm) plays an important role, because it determines the ridge width of the final grating. 20,21 The influence of this effect on the optical performance, namely the extinction ratio of the polarizer, is theoretically calculated for an iridium wire grid polarizer, as shown in Fig. 1(c) and 1(f), and the resist was removed at the final step as shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Wire grid polarizers are well known for their capabilities to generate linearly polarized light from non-polarized light in very broad wavelength ranges [32][33][34][35][36]. Previous studies have shown that spatially non-uniform polarization directions can be generated by using curvilinear nanoslits in Ag films [37].…”
Section: Design and Simulations Of Nanoslit-based Pmmsmentioning
confidence: 99%